Workspaces of Mediation: How Digital Platforms Shape Practices, Spaces and Places of Creative Work - Alica Repenning (Tijdschrift voor economische en sociale geografie, 2022)
This paper investigates how online platforms co-construct spatialities of fashion design. Advancing the notion of workspaces of mediation, the article interlinks research on the geographies of creative work with debates on digital geography. It demonstrates that humans, online platforms, and spatiality are interrelated and come together in the constitution of everyday spatial encounters and experiences. Applying methods from digital ethnography, in-depth interviews, on/offline participant observations, and an analysis of Instagram accounts were conducted. The article demonstrates that Instagram has become a powerful non-human actor that reconfigures (i) practices, (ii) spaces, and (iii) places of work. With the notion of workspaces of mediation, the paper argues that spaces of work must go beyond concepts of hybrid space and beyond the geotag. Instead, mediated workspaces are constituted as a complex entanglement of online and offline socio-spatial relations and practices.
Keywords: 330; Berlin; digital ethnography; digital work; fashion design; mediation; online platforms